Cloud-assisted Outsourcing of Modular Exponentiation Calculation - Zhang, Shuai (International Journal of Computer Science and Information Technology, 2025)
With the rapid development of cloud computing and cluster computing, outsourced computation has become an important means for resource-constrained devices to complete complex tasks, and the outsourcing of modular exponentiation operations has attracted much attention. However, outsourced computation faces security challenges such as privacy, verifiability, and efficiency. This paper reviews existing privacy - preserving schemes for modular exponentiation outsourcing and proposes a privacy - preserving modular exponentiation outsourcing scheme based on secure multi - party computation for a dual - server model. This scheme designs a secure multi - party computation protocol using the Montgomery algorithm to accelerate modular exponentiation outsourcing and improve efficiency. It can protect the entire process of the modular exponentiation outsourcing algorithm, the privacy of data owner information, and the final computation results. Meanwhile, the system model, threat model, and design goals are elaborated in detail, and the correctness, security analysis, and experimental comparison of the scheme are carried out. The research shows that this scheme can ensure accurate and secure computations while achieving high efficiency, providing a more reliable solution for modular exponentiation outsourcing.